Orbital Injuries From Self-Inflicted Gunshots: Patterns, Management, and Visual Outcomes. Issue 2 (March 2020) - Elegbede, Adekunle; Drogt, Carolyn; Wasicek, Philip J.; Dunlow, Ryan; Gebran, Selim; Ngaage, Ledibabari M.; Rasko, Yvonne M.; Liang, Fan; Nam, Arthur J.; Grant, Michael P.
Abstract : Purpose: Self-inflicted facial gunshots (SIGSWs) typically result in a spectrum of severe injuries to facial structures, including the orbit and globe. Roughly three-quarters of those who arrive to the hospital will survive their injuries, and recidivism is typically low. Therefore, effective management is paramount to preserve vision, and long-term quality of life. The objective of this study is to characterize the common injuries to the orbit, globe, and periocular structures following SIGSWs, their management, and their eventual visual and reconstructive outcomes. Methods: Retrospective review of trauma registry records at a Level 1 trauma center for patients who presented alive following SIGSWs involving the globe and/or orbit from 2007 to 2016. Results: Of the 47 patients who presented with SIGSWs to the orbit, 33 (70%) were discharged alive from the hospital. Management strategies for these patients fell into 3 groups, based on the involved structures: i) Open globe injuries (Type I: n = 12, 34%) ii) Orbital fractures with preserved globe and optic nerve (Type II: n = 15, 43%), and iii) Optic nerve injuries with preserved globe (Type III: n = 8, 23%). Compared with Type II and III injuries, patients who had Type I injuries were more likely to die prior to hospital discharge (46% vs. 20% vs. 12%, p = 0.04), undergo ophthalmologic intervention (73% vs. 6% vs. 11%, p = 0.01), and more surgery (6 vs. 3 vs. 0.5 mean surgeries, p < 0.001). Type II injuries most frequently underwent debridement and reconstruction of the bony orbit. Type III and Type I injuries were associated with worse initial and final visual acuity, with the majority (100% and 75%, respectively) having No Light Perception (NLP) on initial exam, and no visual recovery during the follow-up period (median follow up= 25 months). Conclusions: Management and visual outcomes of orbital injuries from SIGSWs is determined by whether the globe and optic nerve are preserved. Open globe injury by itself is associated with higher mortality and significant permanent vision loss. Abstract : Orbital injury from self-inflicted gunshots may result in open globe injury, optic nerve injury and/or orbital fractures. In our cohort, management and prognosis were highly influenced by whether the globe and optic nerve are preserved.